2022
DOI: 10.1073/pnas.2203454119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aceNKPs, a committed common progenitor population of the ILC1 and NK cell continuum

Abstract: The development of innate lymphoid cell (ILC) transcription factor reporter mice has shown a previously unexpected complexity in ILC hematopoiesis. Using novel polychromic mice to achieve higher phenotypic resolution, we have characterized bone marrow progenitors that are committed to the group 1 ILC lineage. These common ILC1/NK cell progenitors (ILC1/NKP), which we call "aceNKPs", are defined as lineage – Id2 + IL-7Rα + CD25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
(252 reference statements)
1
5
0
Order By: Relevance
“…Consistent with their status as immature precursors, ILCp cells retained heterogenous levels of uncommitted progenitor markers c-Kit, PD-1, and CD44 (Figure S2A-B). Furthermore, mature NK and ILC2 cells were low for c-Kit and CD25 with heterogeneous levels of PD-1 and CD44 (Figure S2A-B), in agreement with previous studies (Rodriguez-Rodriguez et al, 2022). Compared to the wildtype mice, ΔTE mice exhibited significantly elevated frequencies and numbers of ILCp and ILC2 cells in the thymus; they also exhibited a moderate increase in the frequencies of NK cells.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with their status as immature precursors, ILCp cells retained heterogenous levels of uncommitted progenitor markers c-Kit, PD-1, and CD44 (Figure S2A-B). Furthermore, mature NK and ILC2 cells were low for c-Kit and CD25 with heterogeneous levels of PD-1 and CD44 (Figure S2A-B), in agreement with previous studies (Rodriguez-Rodriguez et al, 2022). Compared to the wildtype mice, ΔTE mice exhibited significantly elevated frequencies and numbers of ILCp and ILC2 cells in the thymus; they also exhibited a moderate increase in the frequencies of NK cells.…”
Section: Resultssupporting
confidence: 92%
“…AceNKPs uniformly express T-bet and are negative for RORα, RORγt, and GATA3 expression and lack ILC2 and ILC3 developmental potential. 35 Furthermore, tissue resident Lin − Sca1 + Mac1 + (LSM) hematopoietic cells of fetal liver origin in the adult liver can differentiate into liver ILC1s. 36 Single cell analysis combined with pseudotime analysis identified Lin − CD122 + CD49a + precursors downstream of LSM cells with liver ILC1 restricted differentiation potential.…”
Section: Ilc De Velopmentmentioning
confidence: 99%
“…These aceNKPs are characterized as Lin − ID2 + IL7Rα + CD25 − α4β7 − NKG2A/C/E + Bcl11b − cells and can give rise to ILC1/NK cells. AceNKPs uniformly express T‐bet and are negative for RORα, RORγt, and GATA3 expression and lack ILC2 and ILC3 developmental potential 35 …”
Section: Ilc Developmentmentioning
confidence: 99%
“…In contrast, it has been proposed that ILC1s may express one of T-bet or in rarer cases Eomes, but not both [ 15 ]. Recently, a common group 1 ILC progenitor was identified, called aceNKP, which differentiates into a spectrum of group 1 ILCs, indicating that this group is formed of a continuum, rather than discrete populations of cells [ 16 ]. While unlike NK, B and T cells, ILCs are mainly tissue-resident cells [ 17 ], some migration does occur with ILC1s being the main migratory ILC subset [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that functionally, the maturation of NK cells requires the sequential activation of Eomes then T-bet [14]. In contrast, it has been proposed that ILC1s may express one of T-bet or in rarer cases Eomes, but not both [15]. Recently, a common group 1 ILC progenitor was identified, called aceNKP, which differentiates into a spectrum of group 1 ILCs, indicating that this group is formed of a continuum, rather than discrete populations of cells [16].…”
Section: Introductionmentioning
confidence: 99%